2010
DOI: 10.1510/icvts.2009.215848
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban as a substitute of heparin during cardiopulmonary bypass: a safe alternative?

Abstract: Because of unresolved issues like the possibility of clotting in the extracorporeal circuit and prolonged anticoagulation after discontinuing the drug, at present, the use of argatroban as a substitute of heparin during CPB should be restricted to those cases where the other thrombin inhibitors are contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 20 publications
0
34
0
1
Order By: Relevance
“…There is definitely a paucity of data to guide the safe administration of drug in patients requiring CPB, especially in those requiring prolonged CPB runs, and till we have more information, we recommend adding argatroban to the pump prime and to maintain the ACTs between 500 and 600 s. Also, we cannot recommend off-pump over on-pump CABG as data regarding safety of argatroban in off-pump cases is also conflicting. [1821] Though we agree that argatroban can be a good alternative to heparin in select patients, we propose the need for systematic pharmacokinetic studies to help guide argatroban dosing for cardiac surgery involving CPB.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is definitely a paucity of data to guide the safe administration of drug in patients requiring CPB, especially in those requiring prolonged CPB runs, and till we have more information, we recommend adding argatroban to the pump prime and to maintain the ACTs between 500 and 600 s. Also, we cannot recommend off-pump over on-pump CABG as data regarding safety of argatroban in off-pump cases is also conflicting. [1821] Though we agree that argatroban can be a good alternative to heparin in select patients, we propose the need for systematic pharmacokinetic studies to help guide argatroban dosing for cardiac surgery involving CPB.…”
Section: Discussionmentioning
confidence: 97%
“…[17] During CPB using argatroban, there have been concerns with inadequate anticoagulation resulting in clotting of the extracorporeal circuit and at the same time concerns about increased bleeding in the postoperative period because of the latency in normalization of the ACT. Clots in the oxygenator have been reported in the postbypass period after discontinuation of argatroban,[911] but more disconcerting is the fact that people have reported clot formation even during CPB at an ACT of 495 s.[18] Based on these reports, Follis et al . have recently proposed a strategy to keep the ACT between 500 and 600 s.[18]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such underestimation is similar to the effect previously described by Love et al [15] in which a 10% decrease in thrombin time was reported for argatroban-spiked plasma samples containing >600 mg/dL fibrinogen. Because there are no reversal agents for DTIs, elevated levels of these drugs carry the risk of life-threatening bleeding complications [16]. Thus, underestimation of argatroban may exacerbate certain clinical situations and lead to extended coagulopathy [18].…”
Section: Methods Comparisonmentioning
confidence: 99%
“…Son utilisation lors d'intervention de chirurgie cardiaque sous CEC reste limitée à quelques séries de cas. [17][18][19] 8 Aucun antagoniste spécifique à ce traitement n'existe à l'heure actuelle. Chez les patients insuffisants rénaux, l'utilisation de l'hémodialyse s'avère efficace pour l'élimination de la molécule.…”
Section: Danaparoïde Sodiqueunclassified